Development of Low-Cost Electrospinning to Fabricate Structured Nanofiber for Biomedical Designs with Manageable Flowrate and Voltage - Yusro, Muhammad; Kadarisman, Kadarisman (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Electrospinning is the most popular method that uses in nanofiber production. However, the budget to purchase this tool in the market is expensive. This article aims to report on how to build electrospinning on a lesser budget. There are three main components in electrospinning that will be broken down regarding how to build it. First, the syringe pump creates machinery to push the liquid in the syringe creating a Taylor cone affected by high voltage. Second, a high voltage power supply occurs electrostatic force. Third, the collector gathers nanofiber products. This machine has cost Rp 3.168.822 or $220,26. This number is less than the shop production or the previous report to create low-cost electrospinning. To make sure that this method successfully creates nanofiber. Scanning Electron Microscopy (SEM) is conducted and the result shows that the fiber size is 719±0,06 nanometers. Moreover, the flow rate and the voltage also have been assessed resulting that they are in a controllable manner by showing a linear profile. In this article, the budget is shared to declare that this electrospinning is more affordable. Hopefully, this report could help researchers who intend to build electrospinning at the lab scale to develop their research in nanofiber products with less cost.